A systematic review and meta-Analysis of SWARA and WASPAS methods: Theory and applications with recent fuzzy developments - Mardani, Abbas; Nilashi, Mehrbakhsh; Zakuan, Norhayati; Loganathan, Nanthakumar; Soheilirad, Somayeh; Saman, Muhamad Zameri Mat; Ibrahim, Othman (Applied soft computing, 2017)
[Display omitted] •A review of SWARA and WASPAS methods and recent fuzzy developments is presented.•PRISMA approach has been proposed for systematic review and meta-analysis.•Major databases including Web of Science, Scopus and Google Scholar have been selected. The Multiple Criteria Decision Making (MCDM) utility determining approaches and fuzzy sets are considered to be new development approaches, which have been recently presented, extended, and used by some scholars in area of decision making. There is a lack of research regarding to systematic literature review and classification of study about these approaches. Therefore; in the present study, the attempt is made to present a systematic review of methodologies and applications with recent fuzzy developments of two new MCDM utility determining approaches including Step-wise Weight Assessment Ratio Analysis (SWARA) and the Weighted Aggregated Sum Product Assessment (WASPAS) and fuzzy extensions which discussed in recent years. Regarding this, some major databases including Web of Science, Scopus and Google Scholar have been nominated and systematic and meta-analysis method which called “PRISMA” has been proposed. In addition, the selected articles were classified based on authors, the year of publication, journals and conferences names, the technique and method used, research objectives, research gap and problem, solution and modeling, and finally results and findings. The results of this study can assist decision-makers in handling information such as stakeholders’ preferences, interconnected or contradictory criteria and uncertain environments. In addition, findings of this study help to practitioners and academic for adopting the new MCDM utility techniques such as WASPAS and SWARA in different application areas and presenting insight into literature.